2015
DOI: 10.1002/aenm.201501393
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Internal Quantum Efficiency and Stability of Organic Solar Cells via Metallic Nanofunnels

Abstract: Metal nanoparticles are demonstrated to boost the internal quantum effi ciency (IQE) of organic solar cells (OSCs), even without a notable plasmonic optical gain. A hybrid layer platform in combination with silver nanoparticles (AgNPs) and a polyethylenimine-ethoxylated (PEIE) layer maximize the IQE of the OSCs to nearly 100%, yielding a power conversion effi ciency (PCE) of 10.1% in the OSCs. 2D surface characterization confi rmed that the AgNPs provide a short path and funneled charge carriers to the cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
(60 reference statements)
1
23
0
1
Order By: Relevance
“…With [6,6]‐phenyl C 71 ‐butyric acid methyl ester (PC 71 BM) as the acceptor, PTB7:PC 71 BM active layers afforded record power conversion efficiencies (PCEs) higher than 8% in 2011 and soon later higher than 9% among single‐junction BHJ PSCs . Because of high efficiency, the PTB7:PC 71 BM active layer has been widely utilized in electrode modification investigations of BHJ PSCs with various interlayer materials . However, such high PCEs of the PTB7:PC 71 BM active layer were typically achieved with thin active layers of ≈100 nm.…”
Section: Photovoltaic Performances Of Ptb7:pc71bm Active Layers Procementioning
confidence: 99%
“…With [6,6]‐phenyl C 71 ‐butyric acid methyl ester (PC 71 BM) as the acceptor, PTB7:PC 71 BM active layers afforded record power conversion efficiencies (PCEs) higher than 8% in 2011 and soon later higher than 9% among single‐junction BHJ PSCs . Because of high efficiency, the PTB7:PC 71 BM active layer has been widely utilized in electrode modification investigations of BHJ PSCs with various interlayer materials . However, such high PCEs of the PTB7:PC 71 BM active layer were typically achieved with thin active layers of ≈100 nm.…”
Section: Photovoltaic Performances Of Ptb7:pc71bm Active Layers Procementioning
confidence: 99%
“…A more enhanced certified PCE of 9.94% in PTB7‐Th:PC 70 BM OSCs was reported by He et al by controlling the blend ratio of PTB7‐Th and PC 70 BM . Very recently, several researchers also reported high PCEs over 10% by modifying the device structure …”
Section: Device Efficiencymentioning
confidence: 72%
“…Among the PBDTTT derivatives, the representative materials were poly[4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐b:4,5‐b′]dithiophene‐2,6‐diyl][3‐fluoro‐2‐[(2‐ethyl hexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7) and poly[[2,6′‐4,8‐di(5‐ethylhexylthienyl)benzo[1,2‐b;3,3‐b]dithiophene][3‐fluoro‐2[(2‐ethylhexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7‐Th) (Figure a) . Liang et al reported a high PCE of 7.4% in PTB7:PC 70 BM OSCs .…”
Section: Device Efficiencymentioning
confidence: 99%
“…when embedded in a material, MNPs trigger the redistribution of the electromagnetic field by coupling with the incident light at the localized surface plasmon resonance (LSPR) frequency; the light absorption of the surrounding material can be improved via both the increase in the optical‐path length caused by the plasmonic scattering and the near‐field enhancement (NFE)‐induced excitation effects . specifically, MNPs directly attached to a conductive substrate such as the indium tin oxide (ITO) electrode can provide a shorter road of charge flow and facilitate the charge extraction by the nanofunneling effect . moreover, the electromagnetic field around MNPs can also assist to increase the driving force for charge transport .…”
Section: Comparison Of Responsivities and Working Voltages In Perovskmentioning
confidence: 99%
“…The decrease in luminescent lifetime for the hybrid film also demonstrates the effective electron transfer process between perovskites and AuNRs as confirmed by time‐resolved PL measurements (Figure f). Notably, when MNPs are directly attached to the ITO electrode and contacted with the photoactive layer, the generated carriers in the photoactive layer can be funneled and extracted to the ITO electrode through the MNPs under illumination, hence increasing the carrier collection efficiency . This nanofunneling effect enhances charge extraction in structures such as the ITO/AuNRs/perovskites within the hybrid photodetectors.…”
Section: Comparison Of Responsivities and Working Voltages In Perovskmentioning
confidence: 99%